2020
DOI: 10.1073/pnas.1914135117
|View full text |Cite
|
Sign up to set email alerts
|

Siberian and temperate ecosystems shape Northern Hemisphere atmospheric CO 2 seasonal amplification

Abstract: The amplitude of the atmospheric CO2 seasonal cycle has increased by 30 to 50% in the Northern Hemisphere (NH) since the 1960s, suggesting widespread ecological changes in the northern extratropics. However, substantial uncertainty remains in the continental and regional drivers of this prominent amplitude increase. Here we present a quantitative regional attribution of CO2 seasonal amplification over the past 4 decades, using a tagged atmospheric transport model prescribed with observationally constrained flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 88 publications
3
36
0
Order By: Relevance
“…1c). These areas of non-productivity are particularly problematic for future CLM5.0 simulations due to the suspected importance of Siberian CO 2 fluxes for current and future seasonal carbon balance (Zimov et al, 1996(Zimov et al, , 1999Lin et al, 2020). Although we did not cause any additional areas to die, we also did not succeed in increasing productivity in the larch forests of Siberia.…”
Section: Discussionmentioning
confidence: 77%
“…1c). These areas of non-productivity are particularly problematic for future CLM5.0 simulations due to the suspected importance of Siberian CO 2 fluxes for current and future seasonal carbon balance (Zimov et al, 1996(Zimov et al, , 1999Lin et al, 2020). Although we did not cause any additional areas to die, we also did not succeed in increasing productivity in the larch forests of Siberia.…”
Section: Discussionmentioning
confidence: 77%
“…Plant responses to climate change have important implications for future wildlife habitat suitability, surface energy exchange, and carbon fluxes in boreal and tundra regions (Bradshaw et al, 1995; Chapin et al, 2005; Lin et al, 2020; Loranty et al, 2014; Turetsky et al, 2007). However, quantifying these responses across broad and largely inaccessible northern landscapes is a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Since pioneering work by Thoning et al (1989), analysis of the seasonal cycles of atmospheric CO 2 concentrations has been widely used to evaluate carbon exchange dynamics, and the amplitude of the regular seasonal oscillations in atmospheric CO 2 concentrations is a common metric used to infer relative CO 2 uptake. Many studies have combined process-based and atmospheric transport modeling with in situ and airborne observations to infer long-term temporal trends and spatial distributions of seasonal CO 2 exchange, and concluded that Boreal Forest regions play an essential role in global carbon dynamics (Lin et al, 2020;Yin et al, 2018;Piao et al, 2017;Barlow et al, 2015;Bradshaw and Warkentin, 2015;Gauthier et al, 2015;Graven et al, 2013;Pan et al, 2011;Tans et al, 1990). Lin et al (2020) compared seasonal cycle amplitudes (SCA) from surface in situ measurements of CO 2 to those estimated from GEOS-Chem transport modeling coupled with CAMS v17r1 flux estimates, and found that Siberia had the largest SCA of any region considered when normalized for area.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have combined process-based and atmospheric transport modeling with in situ and airborne observations to infer long-term temporal trends and spatial distributions of seasonal CO 2 exchange, and concluded that Boreal Forest regions play an essential role in global carbon dynamics (Lin et al, 2020;Yin et al, 2018;Piao et al, 2017;Barlow et al, 2015;Bradshaw and Warkentin, 2015;Gauthier et al, 2015;Graven et al, 2013;Pan et al, 2011;Tans et al, 1990). Lin et al (2020) compared seasonal cycle amplitudes (SCA) from surface in situ measurements of CO 2 to those estimated from GEOS-Chem transport modeling coupled with CAMS v17r1 flux estimates, and found that Siberia had the largest SCA of any region considered when normalized for area. Furthermore, Lin et al (2020) found that even though Siberia is a relatively small source region, fluxes from Siberia were the second most influential in determining SCA of in situ CO 2 on a global scale, following those from Northern Hemisphere midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation